High-barrier-property full-biodegradable three-layer co-extrusion composite film and preparation method thereof
By adopting a three-layer coextruded composite film structure, polyadipate terephthalate and carbon dioxide-based polyester-polycarbonate materials, the problems of poor toughness and film formation in the prior art are solved, and films with high barrier properties, excellent mechanical properties and fully biodegradable films are achieved, and films with high barrier properties, excellent mechanical properties and fully biodegradable are suitable for a variety of packaging and medical applications.
Patent Information
- Application Number
- CN202510051349.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-18
AI Technical Summary
The prior art is difficult to provide composite films with high barrier properties, excellent mechanical properties and fully biodegradable, especially in the fields of food packaging and medical materials, with poor toughness and film formation difficulties.
A three-layer coextruded composite film structure is adopted, in which the outer layer and the inner layer are composed of polyadipate terephthalate, and the intermediate layer is carbon dioxide-based polyester-polycarbonate. It is prepared by a twin-screw extruder and a three-layer coextruded blowing film unit to achieve good bonding and performance optimization between layers.
It realizes films with high barrier properties and excellent mechanical properties, and has the characteristics of full biodegradation. They are suitable for heat shrink films and packaging fields, reducing costs and improving the economicality of industrialization.
Smart Images

Figure CN119840277A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer composite materials, in particular to a high-barrier fully biodegradable three-layer co-extruded composite film and a preparation method thereof. Background Art
[0002] In order to meet the needs of low-carbon and environmental protection, it is necessary to alleviate the three problems of global warming, oil resource depletion and "white pollution". Biodegradable plastics, as green alternatives to ordinary plastics, can fundamentally solve these problems. Biodegradable plastics that meet the world's recognized biodegradation standards mainly include polylactic acid (PLA), polybutylene succinate (PBS), polybutylene succinate-adipate (PBSA), polybutylene terephthalate-adipate (PBAT), polyhydroxyalkanoates (PHAs), polypropylene carbonate (PPC), polycaprolactone (PCL), etc. Polymethylethylene carbonate (PPC) prepared by copolymerization of propylene oxide and carbon dioxide is the most widely studied carbon dioxide-based polymer. It is a recognized biodegradable material with good light transmittance, high barrier properties and high toughness. It has great application prospects in the fields of food packaging and medical materials. However, due to the shortcomings of poor processing performance, difficult film formation, high self-adhesion, poor thermal stability and mechanical properties of PPC itself, it cannot be used alone and needs to be modified to meet actual needs. We use phthalic anhydride, propylene oxide and carbon dioxide to copolymerize to prepare a completely biodegradable plastic: carbon dioxide-based polyester-polycarbonate (PPC-P) (Chinese patent CN 111378101 A, J.CO2 Util.2021,49,101558). The prepared carbon dioxide-based polyester-polycarbonate has good light transmittance, higher barrier properties, and a mechanical strength of up to 37MPa. Its T g The T of poly(ethylene methyl carbonate) is 40-55℃, which is higher than that of poly(ethylene methyl carbonate) (PPC). g (30-40℃) has been greatly improved. The disadvantage is that it has poor toughness, low elongation at break (~5%), and is a brittle material, which also limits its application in the field of film and food packaging.
[0003] The flexible fatty chains and rigid aromatic chains in poly(butylene terephthalate-adipate-butylene terephthalate) (PBAT) make it highly tough and heat-resistant, while the presence of ester bonds makes it biodegradable. The composite use of poly(butylene terephthalate-adipate-butylene terephthalate) (PBAT) and carbon dioxide-based polyester-polycarbonate (PPC-P) is expected to effectively improve the shortcomings of carbon dioxide-based polyester-polycarbonate (PPC-P), such as difficulty in film formation, high self-adhesion and low toughness.
[0004] Multilayer co-extruded film refers to a co-extruded film with three or more layers and containing barrier materials. This film has the advantages of high barrier, strong function, low cost, flexible structural design, high strength and no pollution. It is suitable for all flexible packaging fields, including food, daily chemicals, beverages, medicine, electronic products, protective films, etc. At present, the application rate of multilayer co-extrusion technology in China has reached 76.9%. It is expected to develop towards more layer structures in the future and expand from the packaging field to more other fields. The commonly used barrier materials in industry mainly include polyvinyl alcohol (PVA), ethylene-vinyl alcohol copolymer (EVOH), nylon (PA), polyvinylidene chloride (PDVC), aluminum foil, etc., but although these materials have excellent barrier properties, they are not biodegradable. The commonly used barrier composite films on the market are almost all composite films composed of polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET) and barrier materials. These composite films are almost impossible to recycle after use, and it is difficult to separate different materials when combined together. The recycling value is very low, and the pollution to the environment may even exceed shopping bags and garbage bags.
[0005] At present, there are many reports on barrier composite films, but few reports on fully biodegradable barrier composite films. Summary of the invention
[0006] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a three-layer co-extruded composite film having high barrier properties, excellent mechanical properties and being fully biodegradable and a preparation method thereof.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] A high barrier fully biodegradable three-layer co-extruded composite film, which is composed of an outer layer, a middle layer and an inner layer;
[0009] The outer layer is composed of the following components in percentage by mass: 80-98% polybutylene adipate terephthalate, 1-19% inorganic filler, and 0.3-2 parts of processing aid;
[0010] The middle layer is a carbon dioxide-based polyester-polycarbonate;
[0011] The inner layer is composed of the following components in percentage by mass: 80-98% of polybutylene adipate terephthalate, 1-19% of inorganic filler, and 0.3-2 parts of processing aid.
[0012] Preferably, in the above-mentioned high barrier fully biodegradable three-layer co-extruded composite film, the polybutylene adipate terephthalate has a melting point of 110-135°C, a melt index of 2-10g / 10min, 2.16kg, 190°C, and a number average molecular weight of 50-120kg / mol.
[0013] Preferably, in the above-mentioned high barrier fully biodegradable three-layer co-extruded composite film, the carbon dioxide-based polyester-polycarbonate is a high molecular polymer obtained by terpolymerization of carbon dioxide, propylene oxide and phthalic anhydride, and has a glass transition temperature of 43-55°C, a melt index of 8-20g / 10min, 2.16kg, 190°C, and a number average molecular weight of 50 to 110kg / mol; its structure is shown in formula (1); wherein m≥1, n≥1, k≥0, and m, n and k are all integers;
[0014]
[0015] Preferably, in the above-mentioned high barrier fully biodegradable three-layer co-extruded composite film, the inorganic filler is one or more of activated talc, calcium carbonate, calcium silicate, mica or white carbon black, and the fineness is ≥1000 mesh.
[0016] Preferably, in the above-mentioned high barrier fully biodegradable three-layer co-extruded composite film, the processing aid is any one of erucamide, oleamide or stearamide.
[0017] Preferably, in the above-mentioned high barrier property fully biodegradable three-layer co-extruded composite film, the thickness of the high barrier property fully biodegradable three-layer co-extruded composite film is between 20-90 μm.
[0018] A method for preparing a high-barrier fully biodegradable three-layer co-extruded composite film comprises the following steps:
[0019] (1) Preparation of poly(butylene terephthalate)-adipate (PBAT) / inorganic filler blown film pellets: poly(butylene terephthalate)-adipate (PBAT), inorganic filler and processing aid are placed in a high-speed mixer in order according to the metered components, stirred evenly and discharged, and then extruded and granulated by a twin-screw extruder to obtain poly(butylene terephthalate)-adipate (PBAT) / inorganic filler blown film pellets, the particle size of which is 3-8 mm, wherein the parameters of melt blending by the twin-screw extruder are temperature / rotation speed of 120°C-150°C-170°C-170°C-170°C-170°C-170°C-170°C-170°C / 150 rpm, and the pulling speed is 5 m / min;
[0020] (2) Preparation of carbon dioxide-based polyester-polycarbonate (PPC-P) blown film pellets: The carbon dioxide-based polyester-polycarbonate (PPC-P) is extruded and granulated through a twin-screw extruder to obtain carbon dioxide-based polyester-polycarbonate (PPC-P) blown film pellets, the particle size of the blown film pellets is 3-8 mm, wherein the parameters of the twin-screw extruder melt blending are temperature / rotation speed of 110°C-130°C-140°C-150°C-150°C-150°C-150°C-140°C-130°C / 150rpm, and the pulling speed is 5m / min;
[0021] (3) The polybutylene terephthalate adipate (PBAT) / inorganic filler blown film pellets and the carbon dioxide-based polyester-polycarbonate (PPC-P) blown film pellets are prepared and transported to a three-layer co-extrusion blown film unit for blow molding to obtain a high-barrier fully biodegradable three-layer co-extrusion composite film; wherein the parameters of the extrusion blown film of the outer layer or the inner layer, the temperature / rotation speed / pulling speed / winding speed are 175°C-180°C-150°C-150°C-150°C-150°C- 150℃-150℃-150℃ / 20rpm / 2.0m / min / 2.2m / min; the parameters of the extrusion blown film of the middle layer carbon dioxide based polyester-polycarbonate (PPC-P), temperature / rotation speed / pulling speed / winding speed are 145℃-150℃-150℃-150℃-150℃-150℃-150℃-150℃-150℃-150℃ / (10-40)rpm / 2.0m / min / 2.2m / min.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) Polybutylene adipate terephthalate (PBAT) has good ductility, elongation at break and tear strength, but has the disadvantages of low modulus, easy curling and deformation, and poor barrier properties. PPCP is an amorphous polymer with high tensile strength and excellent barrier properties, but its elongation at break is low (~5%), and it is a brittle polymer. Therefore, the present invention cleverly prepares PPCP and PBAT into a multilayer composite film. The obtained film combines the properties of the two plastics, retains good ductility and elongation at break, and the strength of the film is also improved. In addition, the comprehensive performance of the film can be adjusted by changing the thickness of different layers to obtain a film with target performance.
[0024] (2) The polybutylene adipate terephthalate and carbon dioxide-based polyester-polycarbonate used in the present invention are both biodegradable plastics, which are a kind of fully biodegradable high-barrier composite film, which is green and environmentally friendly.
[0025] (3) The high barrier fully biodegradable three-layer co-extruded composite film prepared by the present invention can be used in heat shrink film, packaging field, etc. The three-layer film of the present invention has good light transmittance and haze, which enables the three-layer film of the present invention to be more widely used, such as cigarette film in some applications requiring transparent packaging. Compared with pure PBAT, the carbon dioxide-based polyester-polycarbonate used has lower costs, higher economy, and is more conducive to industrialization.
[0026] (4) The high-barrier fully biodegradable three-layer co-extruded composite film prepared by the present invention has high strength, good toughness, high right-angle tear strength, appropriate heat shrinkage rate and good oxygen and water vapor barrier properties.
[0027] (5) Generally, an adhesive layer is required between the layers of a multi-layer film to prevent separation between the layers. However, the carbon dioxide-based polyester-polycarbonate and polybutylene adipate terephthalate used in the three-layer co-extruded composite film of the present invention have good compatibility and can be well bonded without the need for an adhesive, thereby preventing stratification and reducing costs.
[0028] (6) When using PBAT and PPC-P materials to process and form composite films, there is no need to modify existing equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a cross-sectional SEM image of a high barrier fully biodegradable three-layer co-extruded composite film obtained in Examples 4-8 of the present invention;
[0030] Figure 2 The typical stress-strain curve (MD) of the high-barrier fully biodegradable three-layer co-extruded composite film obtained in Examples 4-8 of the present invention;
[0031] Figure 3 It is a macroscopic schematic diagram of the high barrier and fully biodegradable three-layer co-extruded composite film obtained in Examples 1-3 of the present invention and Comparative Examples 1-3. DETAILED DESCRIPTION
[0032] The present invention is further described below with reference to the embodiments.
[0033] The formulation compositions of Examples 1-8 and Comparative Examples 1-3 are shown in Table 1, and the test results of the mechanical properties and barrier properties of the composite films are shown in Table 2.
[0034] Embodiment 1-4 is formed by three-layer co-extrusion blow molding, and the three-layer co-blowing extruder consists of an outer layer extruder, a middle layer extruder and an inner layer extruder. The three-layer co-extruded film with different proportions is obtained by changing the formula. The screw diameter of the outer layer extruder is 50mm, the aspect ratio is 30 / 1, and the barrel temperature is 175-180℃; the screw diameter of the middle layer extruder is 50mm, the aspect ratio is 30 / 1, and the barrel temperature is 145-150℃; the screw diameter of the inner layer extruder is 50mm, the aspect ratio is 30 / 1, the barrel temperature is 175-180℃, and the die head temperature is 150-150-150-150-150-150-150℃. The screw speed of the three layers is the same, which is 20rpm.
[0035] Embodiment 5-8 is formed by three-layer co-extrusion blow molding, and the three-layer co-blowing extruder consists of an outer layer extruder, a middle layer extruder and an inner layer extruder. By changing the thickness of the middle layer, a three-layer co-extruded film with different properties is obtained. The outer layer extruder screw diameter is 50mm, the aspect ratio is 30 / 1, the barrel temperature is 175-180℃, and the screw speed is 20rpm; the middle layer extruder screw diameter is 50mm, the aspect ratio is 30 / 1, the barrel temperature is 145-150℃, and the screw speed is 5-40rpm; the inner layer extruder screw diameter is 50mm, the long diameter is 30 / 1, the barrel temperature is 175-180℃, the screw speed is 20rpm, and the die head temperature is 150-150-150-150-150-150-150℃.
[0036] Comparative Examples 1-3 are formed by a three-layer co-extrusion blow molding method. The three-layer co-blowing extruder consists of an outer layer extruder, a middle layer extruder and an inner layer extruder to obtain three-layer co-extruded films with different inner layers. The screw diameter of the different outer layer extruders is 50mm, the aspect ratio is 30 / 1, and the barrel temperature is 175-180°C; the screw diameter of the middle layer extruder is 50mm, the aspect ratio is 30 / 1, and the barrel temperature is: PPC: 145-150°C, PVA: 190-200°C, PLA: 180-190°C; the screw diameter of the inner layer extruder is 50mm, the aspect ratio is 30 / 1, the barrel temperature is 175-180°C, and the die head temperature is 170-170-170-170-170-170-170°C. The screw speed of the three layers is the same, which is 20rpm.
[0037] Table 1. Composition of Examples 1-8 and Comparative Examples 1-3
[0038]
[0039]
[0040]
[0041] Table 2. Test results of mechanical properties and barrier properties of composite films in Examples 1-8 and Comparative Examples 1-3
[0042]
[0043] Figure 1 The cross-sectional SEM image of the high barrier fully biodegradable three-layer co-extruded composite film obtained in Examples 4-8 of the present invention is shown in FIG. Figure 1 It can be seen that the film has a three-layer structure, as well as the thickness of each layer and the total thickness, and the interface between the layers is blurred, which also shows that the two polymers, carbon dioxide-based polyester-polycarbonate and polybutylene adipate terephthalate, have good compatibility, and the layers can be well bonded without the need for adhesives.
[0044] Figure 2 The typical stress-strain curve (MD) of the high barrier fully biodegradable three-layer co-extruded composite film obtained in Examples 4-8 of the present invention is shown in FIG. Figure 2 It can be seen that the mechanical properties of Examples 4-8 are very good, with the highest tensile strength reaching 31.5MPa and the highest elongation at break reaching 554.5%. Compared with the comparative examples, the comprehensive mechanical properties are the best. Some of the comparative examples have high tensile strength, but low elongation at break, while others have high elongation at break but low tensile strength. Based on the tear strength and barrier properties in Table 2, the high barrier fully biodegradable three-layer co-extruded composite film of the present invention has high tear properties and good barrier properties for oxygen and water vapor, and is a film material with great advantages.
[0045] Figure 3 The macroscopic schematic diagram of the high barrier fully biodegradable three-layer co-extruded composite film obtained in Examples 1-3 of the present invention and Comparative Examples 1-3 is shown in Table 3 and Figure 3 It can be seen that the three-layer film of the present invention has better light transmittance and haze than the comparative film, which can enable the three-layer film of the present invention to be more widely used, such as cigarette film in some applications requiring transparent packaging.
[0046] Table 3. Test results of transmittance and haze of composite films in Examples 1-3 and Comparative Examples 1-3
[0047] example Light transmittance (%) Haze(%) Example 1 89.6±0.2 10.5±0.2 Example 2 88.3±2.3 11.4±1.1 Example 3 88.1±0.6 11.5±1.0 Comparative Example 1 84.0±0.5 12.8±1.4 Comparative Example 2 83.8±0.5 12.1±0.5 Comparative Example 3 83.5±0.4 22.3±1.0
Claims
1. A high barrier fully biodegradable three-layer co-extruded composite film, characterized in that It is composed of three layers: outer layer, middle layer and inner layer. The outer layer is composed of the following components in percentage by mass: 80-98% polybutylene adipate terephthalate, 1-19% inorganic filler, and 0.3-2 parts of processing aid; The middle layer is a carbon dioxide-based polyester-polycarbonate; The inner layer is composed of the following components in percentage by mass: 80-98% of polybutylene adipate terephthalate, 1-19% of inorganic filler, and 0.3-2 parts of processing aid.
2. The high barrier fully biodegradable three-layer co-extruded composite film according to claim 1, characterized in that: The polybutylene adipate terephthalate has a melting point of 110-135° C., a melt index of 2-10 g / 10 min, 2.16 kg, 190° C., and a number average molecular weight of 50-120 kg / mol.
3. The high barrier fully biodegradable three-layer co-extruded composite film according to claim 1, characterized in that: The carbon dioxide-based polyester-polycarbonate is a high molecular polymer obtained by terpolymerization of carbon dioxide, propylene oxide and phthalic anhydride, and has a glass transition temperature of 43-55°C, a melt index of 8-20g / 10min, 2.16kg, 190°C, and a number average molecular weight of 50 to 110kg / mol; its structure is shown in formula (1); wherein m≥1, n≥1, k≥0, and m, n and k are all integers; 4. The high barrier fully biodegradable three-layer co-extruded composite film according to claim 1, characterized in that: The inorganic filler is one or more of activated talc, calcium carbonate, calcium silicate, mica or white carbon black, and the fineness is ≥1000 mesh.
5. The high barrier fully biodegradable three-layer co-extruded composite film according to claim 1, characterized in that: The processing aid is any one of erucic acid amide, oleic acid amide or hard amide.
6. The high barrier fully biodegradable three-layer co-extruded composite film according to claim 1, characterized in that: The thickness of the high-barrier fully biodegradable three-layer co-extruded composite film is between 20 and 90 μm.
7. A method for preparing a high barrier fully biodegradable three-layer co-extruded composite film as claimed in claim 1, characterized in that The steps include: (1) Preparation of poly(butylene terephthalate-adipate-glycol) / inorganic filler blown film pellets: poly(butylene terephthalate-adipate-glycol) ester, inorganic filler and processing aid are placed in a high-speed mixer in order according to the metered components, stirred evenly and discharged, and then extruded and granulated by a twin-screw extruder to obtain poly(butylene terephthalate-adipate-glycol) ester / inorganic filler blown film pellets, the particle size of which is 3-8 mm, wherein the parameters of melt blending by the twin-screw extruder, the temperature / speed are 120°C-150°C-170°C-170°C-170°C -170℃-170℃-170℃-170℃ / 150rpm, traction speed 5m / min; (2) Preparation of CO2-based polyester-polycarbonate blown film pellets: CO2-based polyester-polycarbonate is extruded and granulated through a twin-screw extruder to obtain CO2-based polyester-polycarbonate blown film pellets, the particle size of the blown film pellets is 3-8 mm, wherein the parameters of melt blending in the twin-screw extruder are temperature / rotation speed of 110°C-130°C-140°C-150°C-150°C-150°C-150°C-140°C-130°C / 150rpm, and the pulling speed is 5m / min; (3) The poly(butylene terephthalate-adipate-butylene glycol) / inorganic filler blown film pellets and the carbon dioxide-based polyester-polycarbonate blown film pellets are prepared and transported to a three-layer co-extrusion blown film unit for blow molding to obtain a high-barrier fully biodegradable three-layer co-extrusion composite film; wherein the parameters of the extrusion blown film of the outer layer or the inner layer, the temperature / rotation speed / pulling speed / winding speed are 175°C-180°C-150°C-150°C-150°C-150°C-150°C-150°C-150°C ℃ / 20rpm / 2.0m / min / 2.2m / min; the parameters of the extrusion blown film of the middle layer of carbon dioxide based polyester-polycarbonate, temperature / rotation speed / pulling speed / winding speed are 145℃-150℃-150℃-150℃-150℃-150℃-150℃-150℃-150℃-150℃ / 10-40rpm / 2.0m / min / 2.2m / min.
8. The high barrier fully biodegradable three-layer co-extruded composite film according to claim 1, characterized in that: There is no adhesive layer between the barrier layer and the adjacent plastic film layer of the high-barrier fully biodegradable three-layer co-extruded composite film.
Citation Information
Patent Citations
Polymer film and preparation method thereof
CN102350844A
Three-layer co-extrusion full-degradable mulching film and production process thereof
CN110583326A
Preparation method of biodegradable carbon dioxide-based polyester-polycarbonate terpolymer
CN111378101A
Biodegradable composite film and preparation method thereof
CN115772321A
Barrier biodegradable cigarette packaging film and preparation process thereof
CN116021850A